Percutaneous endoscopic lumbar discectomy via the medial foraminal and interlaminar approaches: A comparative study with 2-year follow-up - Huang, Sen; Wang, Zhenfei; Xu, Long; Bu, Jinhui; He, Bo; Xia, Mengjiao; Chen, Tao; Gao, Juan; Liu, Guangpu; Niu, Ru; Ma, Chao; Liu, Guangwang (Frontiers in Surgery, 2022)
Objective: The purpose of this study was to analyze the clinical effect of PEMFD in the treatment of lumbar disc herniation(LDH). Methods: We retrospectively examined and compared clinical data from 39 single-level LDH patients who underwent PEID and 47 who underwent PEMFD. All the patients were diagnosed with single-level LDH and were treated in Xuzhou Central Hospital for single-segmental lumbar disc herniation between June 2017 and December 2019. Collect and count surgical-related indicators, intraoperative bleeding volume and 24-hour postoperative drainage volume, lower extremity numbness Visual Analogue Scale (VAS), the pain VAS and lumbar Oswestry Disability Index (ODI) scores. Results: Intraoperative bleeding volume and 24-hour postoperative drainage volume were significantly lower in the PEMFD group (p <0.05). Operation time and length of hospital stay did not significantly differ between the groups. Transient spinal cord injury and surgical site infection did not occur. Recurrence occurred in two patients in each group. Repeat surgery in these patients demonstrated remarkable epidural scarring in the PEID group patients; no scarring was evident in the PEMFD group patients. The numbness VAS score 72 hours after surgery and the pain VAS and ODI scores 1 month after surgery significantly differed between groups; however, pain VAS and ODI scores 6, 12, and 24 months after surgery did not. At last follow-up, the modified MacNab criteria outcome did not significantly differ between the groups. Conclusion: PEMFD and PEID have similar short- and medium-term outcomes. However, PEMFD has several advantages: simplicity, lower bleeding volume, and preservation of the LF.